Scaled agile framework. Dealing with software process‐related challenges of a financial group with the action research approach. Issue 6 (19th April 2022) - Kowalczyk, Michał; Marcinkowski, Bartosz; Przybyłek, Adam
Abstract: This article reports on a domain‐specific software development venture at Nordea. We explore organizational constraints, challenges, and corrective actions undertaken when scaling the agile development approach of their Core Banking Platform program. The fit and required customizations of the rather complex and rigid SAFe framework in a policy‐heavy financial institution are audited against the organic growth of the program. In a qualitative study with three cycles using the Action Research method, both organizational and technical restrictions were tackled jointly with the company employees. Thirty‐four potential solutions were developed—some of which turned out to be dead‐ends. Ultimately, the effectiveness of prior recommendations was tested in a highly challenging implementation environment, and the list of guidelines was extended. We discovered several meeting and collaboration schemes that are not fully aligned with previous reports. Abstract : In this work, underlying assumptions of Agile Software Development are challenged when applying the approach at a large scale. We report on a scientifically rigorous Action Research project conducted in a policy‐heavy financial institution to scale up agile practices by tailoring SAFe. We discuss the transformation challenges the organization faced, how we mitigated them, field‐test the effectiveness of the prior recommendations, and extend the list with additional guidelines relevant to other companies seeking to undergo a large‐scale agile transformation.